Portal of Juglandaceae: A comprehensive platform for Juglandaceae study. (15th March 2020) - Guo, Wenlei; Chen, Junhao; Li, Jian; Huang, Jianqin; Wang, Zhengjia; Lim, Kean-Jin
Abstract: Juglandaceae species are plants of great economic value and have been cultivated, domesticated, and utilized by human society for a long time. Their edible, nutrient-rich nuts and tough, durable wood have attracted the attention of botanists and breeders. With the advent of the genomics era, genome sequencing of the Juglandaceae family has been greatly accelerated, and a large amount of data has been generated. In this paper, we introduce the Portal of Juglandaceae (PJU), a tool to bring all these data together. The PJU contains genomes, gene-coding sequences, protein sequences, various types of annotation information, expression data, and miRNA data, which are configured with BLAST, JBrowse, and our self-developed synteny analysis tool. The PJU has a user-friendly and straightforward interface that performs a variety of query tasks with a few simple operations. In the future, we hope that the PJU will serve as a hub for the study of the Juglandaceae family.